Presidential legislation in India : the law and practice of ordinances - Dam, Shubhankar (New Delhi, 2014)
India has a parliamentary system. Yet the president has authority to occasionally enact legislation (or ordinances) without involving parliament. This book is a study of ordinances at the national level in India centered around three themes. Firstly how an artifact of British constitutional history over time became part of India's legislative system. Secondly how when and why presidents resorted to ordinances in post-independent India. Thirdly it analyzes a range of ordinance-related questions including some that are yet to be judicially adjudicated. In the process it explains why much of the Indian Supreme Court's analyses are mistaken and what should take its place. The book explains why the fate of parliamentary reforms may be tied to the reform of this provision for ordinances. Standing at the intersection of constitutional law and political science Presidential Legislation in India offers a new frame through which to understand executive's legislative powers both in parliamentary and presidential systems. http://www.cambridgeindia.org/books/searchedbook/Presidential-Legislation-in-India
Keywords: Orders in council-India